Issues Related to Determining Optimal Management of Patients in Receipt of Disability Benefits - Ebrahim, Shanil (My University, 2013)
Approximately 4.2 million Canadian adults suffer from a physical or psychological disability, of whom up to 30% suffer from depression. Those receiving disability benefits versus those not receiving benefits may be at greater risk of unsatisfactory outcomes because their circumstances or psychological status may interfere with successful implementation of standard therapies. This thesis addresses the effectiveness of therapies for depression in patients receiving disability benefits, using an individual patient data meta-analysis of all published randomized controlled trials evaluating Cognitive Behavioural Therapy and a secondary analysis of an administrative database from a large, private, Canadian insurer. Additionally, this thesis addresses an important methodological issue: assessing the impact of missing participant data for continuous outcomes in systematic reviews. Missing participant data may bias results of individual trials or systematic reviews of individual trials if participants with missing data have different expected outcomes from those with available data. No methods have been proposed for investigating the extent to which missing participant data for continuous outcomes might bias the results of systematic reviews, and this dissertation addresses that gap.
Keywords: Disability Benefits; Optimal Management; Psychotherapy; Depression; Missing Participant Data; Lost to Follow-Up; Mental and Social Health; Rehabilitation and Therapy; Mental and Social Health